Continuity and change in US legal tradition: Evidence from judicial citation communities - Elliott Ash; Caterina Chiopris; Robert Mahari; Suresh Naidu (Proceedings of the National Academy of Sciences, 2026)
Legal doctrine is often described as evolving case by case while preserving coherent legal traditions. We introduce a method for identifying and tracing such traditions by applying the Louvain community-detection algorithm to the complete U.S. federal judicial citation graph (1790–2024; 760,000 opinions linked by 8.3 million citations). The resulting citation communities are unsupervised, blind to court labels and topical taxonomies, yet they form meaningful empirical groupings: In validation exercises, they recover known institutional structure and capture coherent substantive and procedural approaches to law. Using these communities as empirical units, we study how legal traditions evolve and respond to legislative change. We show that the introduction of pivotal federal statutes shifts citation patterns toward newer precedent, indicating that legislation can disrupt established traditions and redirect the development of case law.